2018
DOI: 10.1038/nature25434
|View full text |Cite
|
Sign up to set email alerts
|

Tet2 promotes pathogen infection-induced myelopoiesis through mRNA oxidation

Abstract: Varieties of RNA modification form the epitranscriptome for post-transcriptional regulation. 5-Methylcytosine (5-mC) is a sparse RNA modification in messenger RNA (mRNA) under physiological conditions. The function of RNA 5-hydroxymethylcytosine (5-hmC) oxidized by ten-eleven translocation (Tet) proteins in Drosophila has been revealed more recently. However, the turnover and function of 5-mC in mammalian mRNA have been largely unknown. Tet2 suppresses myeloid malignancies mostly in an enzymatic activity-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
159
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(160 citation statements)
references
References 40 publications
0
159
1
Order By: Relevance
“…TET2 is an epigenetic modifier that is frequently mutated across myeloid malignancies. In CH, TET2 is the second most frequently mutated gene, and growing evidence suggests that factors including secondary genetic alterations [43,44], inflammation [40,45,46], and changes in the microbiota [10] may contribute to the clonal expansion and preleukemic condition of TET2-mutant hematopoietic stem and progenitor cells (HSPCs). Here, we discuss the biological studies investigating environmental influences on HSPCs with TET2 loss of function (LOF) in CH.…”
mentioning
confidence: 99%
“…TET2 is an epigenetic modifier that is frequently mutated across myeloid malignancies. In CH, TET2 is the second most frequently mutated gene, and growing evidence suggests that factors including secondary genetic alterations [43,44], inflammation [40,45,46], and changes in the microbiota [10] may contribute to the clonal expansion and preleukemic condition of TET2-mutant hematopoietic stem and progenitor cells (HSPCs). Here, we discuss the biological studies investigating environmental influences on HSPCs with TET2 loss of function (LOF) in CH.…”
mentioning
confidence: 99%
“…5-hydoxymethyl cytosine is an oxidized product of m 5 C and was originally mapped in Drosophila mRNA (Delatte et al 2016). 5hydoxymethyl cytosine has recently been proposed to be present also in mammalian mRNA (Shen et al 2018). 8oxo-G has also been detected in mRNA, and is largely thought to represent a product of oxidative damage (Shan et al 2003).…”
Section: The History Of the Detection Of Methylated Nucleotides In Mrnamentioning
confidence: 99%
“…A recent study investigating the function of the Tet2 dioxygenase in mice used bisulfite sequencing to identify m 5 C sites that were not converted to 5hmC in Tet2 knockout animals (Shen et al 2018). This revealed that m 5 C and hm 5 C might be used to control mRNA secondary structure and thereby regulate recognition by RNA binding proteins during the immune response (Shen et al 2018).…”
Section: Other Internal Modified Nucleotides In Mrnamentioning
confidence: 99%
“…Our systematic data analyses and exclusive assignment of highly retained, abundant modifications to mRNAs are particularly important in light of the current dialogue regarding prevalence of several mRNA modifications. While the groundbreaking studies that mapped m 5 C and m 1 A to the transcriptome seemed to indicate that these modifications are incorporated at thousands of sites, follow-up reports reach contradictory conclusions -some suggest that these modifications may only be present in a handful of mRNAs, while others support the initial finding that they are common (Edelheit et al 2013;Li et al 2016;Legrand et al 2017;Safra et al 2017;Guallar et al 2018;Shen et al 2018).…”
Section: C Y and M 1 A Are Not Retained At High Levels In Mrna Smentioning
confidence: 99%